The Hyperglycemic Effect of Melatonin in the Chinese Mitten Crab, Eriocheir sinensis - Yang, Xiaozhen; Xu, Minjie; Huang, Genyong; Zhang, Cong; Pang, Yangyang; Yang, Zhigang; Cheng, Yongxu (Frontiers in Physiology, 2018)
Melatonin has been identified in a variety of invertebrate species, but its function is not as well understood as in crustaceans. The effects of melatonin on hemolymph glucose levels and tissue carbohydrate metabolism in the Chinese mitten crab, Eriocheir sinensis, were fully investigated in this study. Moreover, whether the eyestalk (an important endocrine center in invertebrate species) involves in this process or not, also were clarified. Analysis revealed that eyestalk ablation, especially bilateral, caused a significant decrease in the hemolymph glucose level. Moreover, injection of melatonin induced hyperglycemia in a dose-dependent manner both in intact and ablated crabs. Based on the expression of CHH mRNA in the ten different tissues, eyestalk, thoracic ganglion, intestinal tract and hemolymph were selected to estimate the effect of melatonin on the expression of CHH mRNA. Bilateral eyestalk ablation caused a significant increase in the expression of CHH mRNA in the thoracic ganglion, intestinal tract and hemolymph compared with the controls. In addition, injection of melatonin into intact or ablated crabs elevated the CHH mRNA level in the eyestalk, thoracic ganglion and intestinal tract tissues compared with controls. The hemolymph CHH mRNA after melatonin injection was elevated only in ablated crabs. Administration of melatonin resulted in a significant decrease in total carbohydrates and glycogen levels with an increase in phosphorylase activity levels in the hepatopancreas and muscle in intact and ablated crabs. Our findings demonstrated that melatonin can induce hyperglycemic effects in both intact and ablated crabs, suggesting that this effect is probably not mediated solely via eyestalk.